Exploring the determinants of delayed diagnosis of breast cancer in the female population of Punjab (Pakistan) - Farooqi, Samina; Kausar, Samina; Bibi, Kalsoom; Aziz, Zunaira; Rehmat, Tahira (Journal of the Pakistan Medical Association, 2021)
Objective: To explore the factors contributing to late diagnosis of breast cancer in female population of Punjab, Pakistan. Methodology: Descriptive qualitative study with phenomenological approach was used. The study was carried out in University of Health Sciences, Lahore in collaboration with breast cancer clinics/departments of the Jinnah Hospital, Lahore, Sir Ganga Ram Hospital Lahore and Mayo Hospital Lahore. 15 Females diagnosed more than 4 months after appearance of symptoms of breast cancer were recruited using purposive sampling until saturation of data. Data collected through in depth semi structured face to face interviews was tape-recorded, transcribed and then analysed using thematic analysis framework method. Results: Personal/psychological factors, Sociocultural and Health care system related factors were identified as main themes emerged from data. Lack of knowledge, religious believes, use of Alternative medicine, socioeconomic status cultural myths and poorly facilitated health care facility were the most influential determinants of delay among breast cancer patients. Conclusion: Diagnosis delay is very significant health problem in women with breast cancer linked with multiple determinants. However, educating women for recognition of symptoms and reinforcement to pursue for earlier medical consultation will be helpful in reducing breast cancer diagnosis delay in the country. Key terms: Breast Cancer, Metastasis, Delayed Diagnosis, Prognosis, Advance Stage. Continuous...